63=64n

Rewrite the equation as 64n=63.

64n=63

Divide 6 by 3.

64n=2

Multiply each term by n and simplify.

Multiply each term in 64n=2 by n.

64n⋅n=2⋅n

Cancel the common factor of n.

Cancel the common factor.

64n⋅n=2⋅n

Rewrite the expression.

64=2⋅n

64=2n

64=2n

Rewrite the equation as 2n=64.

2n=64

Divide each term by 2 and simplify.

Divide each term in 2n=64 by 2.

2n2=642

Cancel the common factor of 2.

Cancel the common factor.

2n2=642

Divide n by 1.

n=642

n=642

Divide 64 by 2.

n=32

n=32

n=32

Solve for n 6/3=64/n